2009
DOI: 10.1002/jor.20911
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of neutrophil‐derived circulating free DNA (cf‐DNA/NETs) for septic arthritis

Abstract: The release of ''neutrophil extracellular traps'' (NETs) has been identified as a novel immune response in innate immunity. NETs are composed of neutrophil-derived circulating free DNA (cf-DNA) and neutrophil cytoplasm-derived proteins such as proteases. In this study, we analyzed the putative diagnostic value of synovial cf-DNA/NETs for identification of septic arthritis. Forty-two patients with a joint effusion who had undergone arthrocentesis were included. From synovial fluid, cf-DNA/NETs (j-cf-DNA) levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 32 publications
(46 reference statements)
4
56
0
3
Order By: Relevance
“…The observation of Lögters et al [20] in septic arthritis correspond with this findings. Recently different studies started to highlight the role of NETs in different pathological conditions.…”
Section: Nets and Diseasesupporting
confidence: 87%
See 1 more Smart Citation
“…The observation of Lögters et al [20] in septic arthritis correspond with this findings. Recently different studies started to highlight the role of NETs in different pathological conditions.…”
Section: Nets and Diseasesupporting
confidence: 87%
“…Always the short life-span of neutrophils should be taken into account. Activation can be performed by a multitude of reagents, including bacterial LPS, GM-CSF followed by TLR-4 or C5a [20]. The most frequently used reagent is PMA [12,14].…”
Section: Isolation and Activation Of Neutrophilsmentioning
confidence: 99%
“…Whether extracellular traps are beneficial or detrimental to host defense is unclear at this time. Although the potential beneficial effect of trapping and killing extracellular bacterial cells is obvious, the presence of NETs has recently been linked to several human disease states, including systemic lupus erythematosus (27), peritonitis (42,43), vasculitis (30), septic arthritis (31), and pre-eclampsia (25,26). What role macrophage extracellular traps play in host defense and the pathophysiology of infectious diseases will be the subject of future investigations.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10] Before the discovery of NETs, increases in circulating free DNA (cf-DNA) in the blood had been reported in various diseases including several cancers, [11][12][13] trauma, stroke, autoimmune disorders, sepsis and septic arthritis. [14][15][16] This cf-DNA was formerly thought to originate from necrotic and/or apoptotic cells, 17 but several articles have suggested an association between NETs and cf-DNA. [14][15][16][17][18] In these reports, cf-DNA was present both in infectious and noninfectious disease conditions, including a mouse model of lipopolysaccharide-induced shock.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] This cf-DNA was formerly thought to originate from necrotic and/or apoptotic cells, 17 but several articles have suggested an association between NETs and cf-DNA. [14][15][16][17][18] In these reports, cf-DNA was present both in infectious and noninfectious disease conditions, including a mouse model of lipopolysaccharide-induced shock. It was also reported that NETs in capillary vessels might be related to the pathophysiology of disseminated intravascular coagulation.…”
Section: Introductionmentioning
confidence: 99%